The impact of Covid–19 pandemic on the students' communication in English at the University of Muhammadiyah Bone - Jihan Fahrina Salahuddin; Abdul Rahman (Yayasan Cendekiawan Indonesia Timur, 2022)
This study aims to analyze the impact Covid-19 era on the student's English communication at the University Muhammadiyah Bone. This research applied a descriptive qualitative research method. It finds that every respondent is average in speaking skills based on pronunciation and vocabulary and finds that movies and songs are all subjects easy to accept as tools to learn and study English before and after Covid-19 existed in the world. The data collection techniques of this research used triangulation consisting of questionnaires, interviews, and documentation. The data were analyzed using 6 steps: organizing and preparing the data, then reading and looking the data, coding, making descriptions, representing the data, and finally finding the result. The result showed that the impact Covid-19 pandemic on the student's communication in English at the University Muhammadiyah Bone are positive and negative impacts and also only in how the class changes from offline to online that every subject has said that the ability is not different or reduced but communication often does in virtual not face to face. The student's problem in communication that happens is shyness, all subjects are afraid that people do not understand what they said but mostly said that practice is helping them to reduce it.